RELATIONSHIP BETWEEN PLANKTON COMMUNITY STRUCTURES WITH WATER QUALITY IN RIAM KANAN RIVER SUBDISTRICT KARANG INTAN - Rani Sasmita; Krisdianto Krisdianto; Adriani Adriani (Universitas Lambung Mangkurat, 2009)
This study aimed to verify the relationship between plankton community structures (abundance, diversity index, uniformity index, dominance) with the water quality in Karang Intan River Subdistrict Riam Kanan. The benefits of this research, providing scientific information about environmental parameters that influence the plankton community structure. Based on this research, water quality parameters related (significant correlation) with a plankton community structures were dissolved oxygen, ammonia, nitrate, phosphate, brightness and water current.